2016
DOI: 10.1088/1748-9326/11/5/054017
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and projections for the Barents region: what is expected to change and what will stay the same?

Abstract: We present an outlook for a number of climate parameters for temperature, precipitation, and storm statistics in the Barents region. Projected temperatures exhibited strongest increase over northern Fennoscandia and the high Arctic, exceeding 7°C by 2099 for a typical 'warm winter' under the RCP4.5 scenario. More extreme temperatures may be expected with the RCP8.5, with an increase exceeding 18°C in some places. The magnitude of the day-to-day variability in temperature is likely to decrease with higher tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
(33 reference statements)
3
17
0
Order By: Relevance
“…However, the EC-EARTH driven run still gives interesting insights on how the COSMO-CLM performs and how the projected changes are influenced by the driving model. These results are in agreement with other studies covering the same area (Benestad et al, 2016;Koenigk et al, 2015;Førland et al, 2009;Vikhamar-Schuler et al, in press), including both sta-275 tistical and dynamical downscaling approaches. Compared with the big ensemble of statistically downscaled models shown in Benestad et al (2016) our projections cover a large part of the projected uncertainties.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the EC-EARTH driven run still gives interesting insights on how the COSMO-CLM performs and how the projected changes are influenced by the driving model. These results are in agreement with other studies covering the same area (Benestad et al, 2016;Koenigk et al, 2015;Førland et al, 2009;Vikhamar-Schuler et al, in press), including both sta-275 tistical and dynamical downscaling approaches. Compared with the big ensemble of statistically downscaled models shown in Benestad et al (2016) our projections cover a large part of the projected uncertainties.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with other studies covering the same area (Benestad et al, 2016;Koenigk et al, 2015;Førland et al, 2009;Vikhamar-Schuler et al, in press), including both sta-275 tistical and dynamical downscaling approaches. Compared with the big ensemble of statistically downscaled models shown in Benestad et al (2016) our projections cover a large part of the projected uncertainties. This can be attributed to the use of an ESM and scenario combination in this study, which covers weak (MPI-ESM-LR RCP2.6), moderate (MPI-ESM-LR RCP4.5) and strong (MPI-ESM-LR RCP8.5 and EC-EARTH RCP4.5) climate change signals over the target region.…”
Section: Discussionsupporting
confidence: 92%
“…They conclude that the volatility of the winter temperature (December, January and February) is decreasing. Benestad et al (2016) draw a similar conclusion based on climate model data that the day-to-day variability in temperature in the Barents region is likely to decrease with higher temperatures. The diverging conclusions are influenced by application of, respectively, different methods, time scale, data from different geographical regions and time periods.…”
Section: Climate Change and The Likelihood Of A Snow-and Ice-free Wintersupporting
confidence: 63%
“…These environmental changes have been reflected in known phenological changes in both plants and pollinators (Høye et al 2007, Høye and Forchhammer 2008, Schmidt et al 2016. Combined with the increase in severe weather and other perturbations due to climate change (Hassol 2004, Adger et al 2007, Steiner et al 2015, Benestad et al 2016, these phenological shifts imply that changes in which species are observed at a site and changes to species' roles may both increase as the Arctic continues to warm. Determining the amount of change caused by climate change versus random fluctuations is beyond the scope of the present study since the networks were observed at only four time points clustered fifteen years apart.…”
Section: Changing Roles In the Arcticmentioning
confidence: 99%